(untitled) (Research, Society and Development, 2022)
Objective: To review the literature on the main oral alterations found in pediatric patients with Acute Lymphoblastic Leukemia, whether caused by the disease or by antineoplastic treatment. Methodology: This is an integrative literature review that used the PubMed, Lilacs and Scielo databases through the keywords registered in the Health Sciences Descriptors (DeCS), in which studies that addressed the proposed theme were included. in this work, available in the aforementioned databases, in English and Portuguese, between the years 2011 to 2021. Results: 514 articles were found, of these 178 were initially screened based on titles and abstracts and only 34 articles met the eligibility criteria. Conclusion: Acute Lymphoblastic Leukemia, in most cases, leads to the appearance of oral lesions resulting from the disease, especially in the gingival regions, buccal mucosa, floor of the mouth, hard and soft palate. Chemotherapy and radiotherapy for Acute Lymphoblastic Leukemia are effective antineoplastic therapies, however, their side effects affect the oral cavity, with the most recurrent oral complications being: mucositis, candidiasis and radiation caries. It is of great value that the dentist is inserted in the multidisciplinary context, at the hospital and oncological level, as part of the success of the treatment of this leukemia, whether as a preventive or therapeutic approach.